The Effectiveness of Foreign Exchange Market Intervention: A Review of Post-2001 Studies on Japan - Takagi, Shinji (Journal of Reviews on Global Economics, 2014)
Post-2001 studies on Japanese official intervention, though divergent in results, generally support the effectiveness of daily intervention in influencing yen-dollar exchange rate returns. Studies are less conclusive about the impact on volatility. Any impact of intervention appears to be short-lived and a reversal of the initial impact to occur on subsequent days, suggesting market microstructure as the primary channel: intervention acts like any other information and works through order flows. The overriding message of the literature is that the impact of intervention depends on the conditions under which it takes place. Each intervention is thus a unique event. This explains why econometric tests of the average impact of intervention yield mixed results.